(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Potato is the third important food crop in Bangladesh and Bangladesh ranked as third and seventh in Asia and in the world, respectively. But potato production greatly affected by the late blight of potato caused by an oomycete, Phytophthora infestans (Mont.) de Bary worldwide. Application of need-based fungicides is the key factor to control this disease and to avoid development of fungicide resistance in P. infestans. Experiments were conducted in both in vitro and in field condition to evaluate some selected chemical fungicides to identify the best one to control the late blight disease of potato. The results of in vitro test revealed that all the fungicides inhibited the growth of P. infestans by 94% over control. But the results of field experiment conceded that the lowest late blight severity was found in T10 (Curzate M8) (0.49%) followed by T6 (AcrobateMz) (0.52%), T8 (Micra) (0.59%), T7 (Xtramyl) (0.61%), T3 (Daconyl) (0.84%), T5 (Secure) (1.28%), T9 (Sanoxanyl) (1.43%), T1 (Unilax) (1.83%), T2 (TemperM) (2.58%) and T4 (Amiscore) (6.34%) at 71 DAP while the maximum late blight severity (95.33%) was observed in T0 (water as control). The highest yield was obtained in T10 (Curzate M8) (25.94 t/ha) followed by T6 (AcrobateMz) (25.67 t/ha), T5 (Secure) (25.22 t/ha), T7 (Xtramil) (24.61 t/ha), T8 (Micra) (24.61 t/ha) and T9 (Sanoxanil) (23.67 t/ha) which were statistically similar and the lowest (8.39 t/ha) yield was observed in T0 (water as control). The highest Benefit Cost Ratio (BCR) was obtained from when potato plants were sprayed with T10 (Curzate M8) (1.02) following by T7 (Xtramil) (0.99), T8 (Micra) (0.99), T6 (AcrobateMz) (0.92), T9 (Sanoxanil) (0.90), T5 (Secure) (0.89), T1 (Unilax) (0.80), T3 (Daconil) (0.74), T4 (Amiscore) (0.71) and T2 (TemperM) (0.44) compared to control T0 (water as control) (-0.30). The results indicated that application of these fungicides yielded a benefit of Tk. ranged by 0.44 to 1.02 over the investment of Tk. 1.00. Therefore, identification of a number of potential chemical fungicides might be useful in the alternate use of these fungicides against late blight of potato in the field. Asian Australas. J. Biosci. Biotechnol. 2022, 7 (1), 23-35